2013
DOI: 10.1016/j.ajog.2013.08.020
|View full text |Cite
|
Sign up to set email alerts
|

The association of dysmenorrhea with noncyclic pelvic pain accounting for psychological factors

Abstract: OBJECTIVE The factors that underlie pelvic pain are poorly understood. Specifically, the relative influence of dysmenorrhea and psychological factors in the etiology of noncyclic pelvic pain conditions, such as interstitial cystitis and irritable bowel syndrome, is unknown. To further characterize pelvic pain, we compared the frequency of menstrual, somatosensory, and psychological risk factors between women with and without severe noncyclic pelvic pain symptoms. STUDY DESIGN A total of 1012 reproductive-age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 40 publications
2
51
0
1
Order By: Relevance
“…Since self-reported symptom indices are vulnerable to somatization and psychological factors, complete phenotypic assessment of pain states ideally includes symptom-based and unbiased experimental visceral pain assessment. 8,22,23 Third, we used a positive control group without significant bladder symptoms to untangle potential pain and urgency relationships on visceral pain sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Since self-reported symptom indices are vulnerable to somatization and psychological factors, complete phenotypic assessment of pain states ideally includes symptom-based and unbiased experimental visceral pain assessment. 8,22,23 Third, we used a positive control group without significant bladder symptoms to untangle potential pain and urgency relationships on visceral pain sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic pain conditions are associated with increased pain sensitivity due to central changes in the nervous system, as well as other factors that affect the neurobiology of pain (e.g. sleep fragmentation) .…”
Section: Introductionmentioning
confidence: 99%
“…showed that 81% of women with CPP also experience dysmenorrhoea. A study by Westling et al . also found a significant association between dysmenorrhoea and noncyclic pelvic pain (defined as dyspareunia, dyschezia or dysuria), suggesting that dysmenorrhoea may be an aetiological factor.…”
Section: Introductionmentioning
confidence: 96%